Some evidence on late bidding in eBay auctions - Ladislav Wintr (National Bank of Belgium, 2008)
Bidding in the last seconds or minutes of an auction is a common strategy in Internet auctions with fixed end-times. This paper examines the three explanations of late bidding in eBay auctions that survived the first scrutiny in Roth and Ockenfels (2002). There is no indication that late bidding could lead to collusive gains for bidders. Late bidding is a strategic response to the presence of bidders placing multiple bids. Experts protecting their private information are typically the last to bid while collectors are often the first. As bidders gain familiarity with eBay rules, they tend to bid slightly earlier
Keywords: D44; 330; Online Auctions; Internet; Late Bidding; eBay; Auktion; Internetportal; E-Business; Zeit; Kartell; USA